2013
DOI: 10.1111/srt.12095
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes in skin of different phototypes under the action of topical corticosteroid therapy and tacrolimus

Abstract: Recording of early preclinical signs of epidermis thinning in the course of OCT follow-up may be an indication for changing the corticosteroid therapy by calciumneurin inhibitors, which will permit to individualize the therapy, to increase its efficacy, and to minimize the possibility of complications in each particular case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Non‐invasive study of skin morphology is of utmost importance to the understanding of the skin's changes in physiological and pathological conditions. Understanding different skin types and conditions, and monitoring changes created by the application of topical products, has become increasingly fundamental in providing scientific validation of product claims in cosmetic science 29–35 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non‐invasive study of skin morphology is of utmost importance to the understanding of the skin's changes in physiological and pathological conditions. Understanding different skin types and conditions, and monitoring changes created by the application of topical products, has become increasingly fundamental in providing scientific validation of product claims in cosmetic science 29–35 …”
Section: Discussionmentioning
confidence: 99%
“…The absence of any damage and alteration of tissue allows for the study of tissue dynamics and the effects of interventions on skin at different times and on cosmetically sensitive areas. Consequently, there has been an increasing use of these imaging modalities in the dermo‐cosmetic field and industry to study skin pathophysiology, to test skin care products and to test the effects of various therapies 29–35 …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, TACo was found to preserve skin barrier integrity and function, and has previously been shown not to thin the epidermis. 24 Another human study found that pimecrolimus 1% cream applied twice daily for 3 weeks preserved normal lipid bilayer structures and lamellar body extrusion. 23 Unlike BMV, pimecrolimus upregulates the expression of genes important in maintaining skin barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…21 Furthermore, care must be taken when it is combined with topical corticoids due to its associated effect on these (epidermal atrophy, hypertrichosis, hypopigmentation, cutaneous fragility, telangiectasia, stretch marks). 22 In spite of the questions raised, other authors defend the safety of HQ given that when reviewing the incidence of exogenous ochronosis in the United States, they found that this was scarce. 23 In this study, we have demonstrated that the treatment of melasma with the protocol of the new combination product obtains a significant improvement in the MASI vs. the vehicle-treated side.…”
Section: Discussionmentioning
confidence: 99%